Role of human urinary kallikrein in reducing progressive ischemic stroke among acute ischemic stroke patients with concurrent hypertension and diabetes: a hospital-based retrospective cohort study - Zheng, Zeyang; Li, Yuelong; Yang, Shanshan; Xu, Yuanqi; Yi, Lian; Liu, Yushuang; Zhang, Li; Zhang, Zhongling (Frontiers in Neurology, 2025)
BackgroundProgressive ischemic stroke (PIS) poses significant challenges in the management of acute ischemic stroke (AIS), with higher morbidity and mortality rates, especially among patients with vascular risk factors such as hypertension and diabetes. This study evaluates the efficacy of human urinary kallidinogenase (HUK) in reducing the incidence of PIS in patients with AIS, with a particular focus on subgroups based on vascular pathology and thrombolytic treatment.MethodsThis retrospective cohort study included 916 patients with AIS treated at a single tertiary care center between January 2022 and September 2023. The patients were divided into two groups based on whether they received HUK treatment in addition to standard care or standard care alone. The primary outcome was the incidence of PIS. Independent sample t-tests or chi-squared tests were used for univariate analysis between groups to identify potential predictors associated with the occurrence of PIS, with factors achieving a p-value < 0.1 considered for multivariate binary logistic regression analysis. Multivariate analysis adjusted for potential confounders to determine independent predictors significantly associated with PIS. The significance threshold was set at p < 0.05. In addition, subgroup analyses were conducted based on stroke subtype (TOAST classification), thrombolysis treatment, and infarction location.ResultsHUK treatment significantly reduced the incidence of PIS (p < 0.001), with the most notable effects observed in patients with large-artery atherosclerosis and small-artery occlusion, those not undergoing intravenous thrombolysis, and those with anterior circulation infarctions. Conversely, no significant reduction was noted in patients with cardioembolic stroke, other etiologies of infarction, intravenous thrombolysis, posterior circulation infarctions, or both anterior and posterior circulation infarctions. Factors such as low body mass index (BMI) and high activated partial thromboplastin time are associated with an increased risk of PIS.ConclusionHUK treatment appears to be an effective strategy for reducing the risk of PIS in patients with AIS, particularly in those at higher risk owing to specific vascular pathologies. These findings support the use of HUK in clinical practice to improve the outcomes of patients with stroke. Future prospective, multicenter, randomized controlled trials are warranted to validate these findings and further elucidate the underlying mechanisms.